PENGARUH EDUKASI GIZI MELALUI MEDIA VIDEO PIRING MAKANKU TERHADAP PENGETAHUAN DAN SIKAP SISWA - Sutrio Sutrio; Andi Eka Yunianto (Jurnal Gizi Prima (Prime Nutrition Journal), 2021)
Background : The problem of nutrition in adolescents, especially the problem of obesity, is one of the focuses of government attention. Nutrition education is one of the most effective ways to increase the knowledge and attitudes of adolescents to maintain their diet so that obesity does not occur. Purpose : This study purposed to analyze the effectiveness of nutrition education in the video media "Piring Makanku" towards increasing the knowledge and attitudes of students at SMP Negeri 1 Tumijajar. Methods : The design in this study was a quasi-experiment. The sample in this study amounted to 30 students of class IX through random sampling divided into 2 groups, namely intervention and control . The Mann-Whitney test was used to analyze differences in the effectiveness of nutrition education on students' knowledge and attitudes. Results : The education provided was able to increase students' knowledge (p = 0.001) and attitudes (p = 0.001) in both the intervention group and the control group. Conclusion : Nutrition education is effective in increasing students' knowledge and attitudes.  Background : The problem of nutrition in adolescents, especially the problem of obesity, is one of the focuses of government attention. Nutrition education is one of the most effective ways to increase the knowledge and attitudes of adolescents to maintain their diet so that obesity does not occur. Purpose : This study purposed to analyze the effectiveness of nutrition education in the video media "Piring Makanku" towards increasing the knowledge and attitudes of students at SMP Negeri 1 Tumijajar. Methods : The design in this study was a quasi-experiment. The sample in this study amounted to 30 students of class IX through random sampling divided into 2 groups, namely intervention and control . The Mann-Whitney test was used to analyze differences in the effectiveness of nutrition education on students' knowledge and attitudes. Results : The education provided was able to increase students' knowledge (p = 0.001) and attitudes (p = 0.001) in both the intervention group and the control group. Conclusion : Nutrition education is effective in increasing students' knowledge and attitudes.   ABSTRAK  Latar Belakang : Masalah gizi pada remaja terutama masalah kegemukan menjadi salah satu fokus perhatian pemerintah. Edukasi gizi adalah salah satu cara yang yang efektif dalam meningkatkan pengetahuan dan sikap remaja untuk menjaga pola makan agar tidak terjadi kegemukan. Tujuan : Penelitian ini bertujuan untuk menganalisis efektifitas edukasi gizi media video “Piring Makanku” terhadap peningkatan pengetahuan dan sikap siswa di SMP Negeri 1 Tumijajar. Metode : Desain penelitian ini adalah quasi experiment. Sampel pada penelitian ini berjumlah 30 siswa kelas IX dengan cara random sampling yang terbagi 2 kelompok yaitu intervensi dan kontrol. Uji Mann-Whitney digunakan untuk menganalisis perbedaan efektivitas edukasi gizi terhadap pengetahuan dan sikap siswa. Hasil : Edukasi yang diberikan dapat meningkatkan pengetahuan (p=0,001) dan sikap (p=0,001) siswa baik pada kelompok intervensi dan kelompok kontrol. Kesimpulan : Pemberian edukasi gizi melalui media video berpengaruh terhadap meningkatan pengetahuan dan sikap siswa.